2005
DOI: 10.1242/jeb.01792
|View full text |Cite
|
Sign up to set email alerts
|

Effect of food quality, distance and height on thoracic temperature in the stingless beeMelipona panamica

Abstract: Corrigendum Nieh, J. C. and Sánchez, D. Effect of food quality, distance and height on thoracic temperature in the stingless bee Melipona panamica. J. Exp. Biol. 208,[3933][3934][3935][3936][3937][3938][3939][3940][3941][3942][3943] On the title page of this paper, Daniel Sanchez was incorrectly affiliated to Division of Biological Sciences, Section of Ecology, Behavior, and Evolution, University of California San Diego, MC#0116, 9500 Gilman Drive, La Jolla, CA 92093-0116, USAThe correct affiliation should ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 58 publications
2
13
0
Order By: Relevance
“…Also, foragers maintained a higher thoracic temperature excess (A7VH) relative to ambient temperature and feeder temperature at low ambient temperatures (A77 A cold: 13.30°C±2.39°C, A7% normal: 6.47°C±1.40°C, f<0.0001; Fig. 6a,b), as Nieh and Sanchez (2005) predicted for M. panamica.…”
Section: Effect Of Feeder and Air Temperature On T Thsupporting
confidence: 71%
See 4 more Smart Citations
“…Also, foragers maintained a higher thoracic temperature excess (A7VH) relative to ambient temperature and feeder temperature at low ambient temperatures (A77 A cold: 13.30°C±2.39°C, A7% normal: 6.47°C±1.40°C, f<0.0001; Fig. 6a,b), as Nieh and Sanchez (2005) predicted for M. panamica.…”
Section: Effect Of Feeder and Air Temperature On T Thsupporting
confidence: 71%
“…These results raised interesting possibilities about stingless bee foragers being able to regulate body temperature according to net food profitability, as has been shown in other Hymenoptera (e.g., Apis mellifera, Paravespula vulgaris, Kovac and Stabentheiner 1999;Bujok et al 2002). Nieh and Sanchez (2005) recently tested this possibility in the stingless bee, Melipona panamica. Using infrared thermography, they showed that M. panamica foragers can elevate their thoracic temperature in response to profitable food sources (higher sucrose concentration, location closer to the nest) on the feeder and inside the nest.…”
Section: Introductionmentioning
confidence: 79%
See 3 more Smart Citations